Silicon carbon material as well as preparation method and application thereof

Composite carbon fibers were prepared by high-voltage electrospinning and vapor deposition techniques, and spherical silicon particles were embedded to form a stable conductive network. This solved the problems of high impedance and volume expansion of silicon-carbon anode sheets, and improved the electrical performance and cycle stability of lithium-ion batteries.

CN121023809APending Publication Date: 2025-11-28WANXIANG 123 CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511244408.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing carbon nanofiber conductive agents cannot form a stable and continuous conductive network in an aqueous environment, resulting in high impedance of silicon-carbon anode sheets. Furthermore, silicon materials undergo severe volume expansion during lithium intercalation, affecting battery cycle performance.

Method used

Continuous carbon fibers were prepared using high-voltage electrospinning technology, and carbon nanofibers were promoted to grow by metal salts to form carbon fibers with large specific surface area and pore size. Spherical silicon particles were embedded in the carbon fibers, and carbon coating was formed by vapor deposition to construct a stable conductive network and suppress the expansion of silicon particles.

Benefits of technology

It significantly reduces electrode impedance, improves battery electrical and cycle performance, reduces electrode thickness rebound rate under full charge, and enhances battery stability and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention discloses a silicon-carbon material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The preparation method of the silicon-carbon material comprises the following steps: S1, mixing a carbon source and metal salt, and carrying out dry ball milling to obtain particles D50lt of the mixture; 10 [mu] m; the mixture is mixed with an aprotic polar solution, and continuous fibers with the diameter being 300 + / -50 nm are spun through high-voltage electrostatic spinning; s2, in the atmosphere of inert gas, heating the continuous fibers to 750-850 DEG C, and keeping the temperature; raising the temperature to 1800-2200 DEG C in the atmosphere of hydrogen and inert gas, carrying out high-temperature reduction reaction, and keeping the temperature; then heating to 2800-3200 DEG C in an inert gas atmosphere, and carrying out heat treatment to obtain pore-forming carbon fibers; s3, enabling spherical silicon particles with the particle size of 100-150nm to permeate into pores of the pore-forming carbon fibers; and S3, carrying out carbon coating on the silicon-carbon composite material through vapor deposition. According to the silicon-carbon material disclosed by the invention, silicon particles are embedded into carbon fiber pores, so that the electrical property of a lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lithium ion batteries, in particular to a silicon-carbon material and a preparation method and application thereof. BACKGROUND

[0002] The importance of lithium ion batteries is revolutionary, which has profoundly changed the way of energy storage, utilization and mobility in human society, and is one of the core driving forces of contemporary technological development and green transformation. It can be said that without the maturity and popularity of lithium ion battery technology, the mobile Internet lifestyle we are familiar with today, the booming electric vehicle industry and the rapid advancement of the energy revolution would be difficult to achieve. It is one of the most disruptive and influential technologies in the 21st century, and its importance will continue to grow in the next few decades. The negative electrode sheet is one of the indispensable core components of lithium ion batteries, and its importance lies in its decisive influence on the performance, safety, life and cost of the battery. Without an efficient and stable negative electrode sheet, lithium ion batteries cannot realize their key advantages.

[0003] With the expansion of the application scenarios of lithium ion batteries, customers have new requirements for the energy density of lithium ion batteries. The traditional graphite negative electrode active material cannot further improve the energy density of the battery due to its limited capacity (about 360 mAh / g). Silicon material with a theoretical capacity of up to 4200 mAh / g makes it a new lithium ion battery active material. Silicon-carbon material is composed of carbon material and silicon material. Carbon material has good electrical conductivity and stability, while silicon material has high specific capacity. During charging, lithium ions migrate from the positive electrode to the negative electrode through the electrolyte, while lithium ions in the carbon material and silicon material are intercalated and deintercalated, realizing the storage and release of lithium ions. Carbon-silicon negative electrode batteries have high specific capacity and low voltage platform, which can provide more energy storage.

[0004] The existing carbon nanofiber conductive agent is used in the silicon-carbon negative electrode system, and the conductive agent and the silicon-carbon negative electrode have poor dispersing ability in the aqueous environment. Even if a carbon nanotube or carbon nanofiber conductive agent with strong electrical conductivity is used, a stable and continuous conductive network cannot be formed, resulting in large impedance of the silicon-carbon negative electrode sheet, which is not conducive to various electrical properties. At the same time, the volume of silicon expands by 200% when it is fully intercalated with lithium. The higher the silicon content, the higher the strength requirement of the current collector. Due to the large volume expansion of the silicon negative electrode, the rebound rate of the negative electrode sheet under the full charge state is increased, affecting the subsequent cycle performance. SUMMARY

[0005] The present application relates to the technical field of lithium ion batteries, in particular to a silicon-carbon material and a preparation method and application thereof.

[0006] A method for preparing a silicon-carbon material, characterized by comprising the following steps:

[0007] S1 Preparation of precursor: A carbon source and a metal salt are mixed and dry ball-milled until the particle size D50 of the mixture is <10μm; the mixture is mixed with an aprotic polar solution and spun into continuous fibers with a diameter of 300±50nm by high-voltage electrospinning.

[0008] S2 pyrolysis and purification: In an inert gas atmosphere, the continuous fiber is heated to 750-850℃ and held at that temperature; then in an atmosphere of hydrogen and inert gas, the temperature is raised to 1800-2200℃ for a high-temperature reduction reaction and held at that temperature; then in an inert gas atmosphere, it is heated to 2800-3200℃ for heat treatment to obtain porous carbon fiber.

[0009] S3 silicon-carbon composite: Spherical silicon particles with a particle size of 100-150nm are infiltrated into the pores of porous carbon fibers.

[0010] S3 Carbon Coating: Carbon coating of silicon-carbon composite materials is performed by vapor deposition.

[0011] Metal salts can be iron-based salts such as ferric chloride (FeCl3·6H2O) and ferrous sulfate (FeSO4·7H2O); or zinc-based salts such as zinc acetate (Zn(CH3COO)2) and zinc chloride (ZnCl2); or bimetallic salt complexes such as nickel nitrate / cobalt nitrate (Ni(NO3)2 / Co(NO3)2) and ferric oxalate / manganese oxalate (FeC2O4 / MnC2O4). They volatilize into gas at 2000℃ and can be used as pore-forming materials.

[0012] During the precursor preparation process, a high-temperature volatile metal salt is added, which increases the diameter of the carbon nanofibers from the conventional 150 nm to 300 nm during growth, thereby improving the specific surface area and pore size of the carbon nanofibers. Spherical silicon particles are embedded in the pores of the porous carbon fibers, and the good mechanical strength of the carbon fibers suppresses the expansion of the silicon particles, solving the problem of large thickness rebound of the electrode under full charge and improving the battery cycle performance.

[0013] Vapor deposition forms a continuous, dense carbon coating, which can improve its initial coulombic efficiency and cycling performance.

[0014] The silicon-carbon material prepared by this invention has silicon particles embedded in the pores of carbon nanofibers to form a stable conductive network, which significantly reduces electrode impedance and cell DCR, and improves various electrical performances of the battery.

[0015] By stretching and solidifying polymer solutions or melts using a high-voltage electrostatic field, ultrafine fibers with diameters ranging from nanometers to micrometers are formed. The fiber surface exhibits typical thermoplastic polymer characteristics and can be oriented and arranged by collecting with rollers, significantly improving the conductivity and mechanical properties of the fibers.

[0016] Furthermore, in step S1, the carbon source accounts for 70-85% of the mass of the mixture.

[0017] Furthermore, in step S1, the carbon source includes one or more of high-purity lignin sulfonate, alkali lignin, organic solvent lignin, polyaniline, polypyrrole, polyacrylonitrile, and polyvinyl alcohol; the metal salt is a soluble salt of iron and zinc.

[0018] Carbon sources provide the main carbon framework. Metal salts provide pore-forming and catalytic functions.

[0019] Furthermore, the metal salt is ferric nitrate and zinc nitrate, and the ferric nitrate accounts for 30-40% of the total mass of the metal salt.

[0020] Ferric nitrate provides oxidation catalysis, promoting the graphitization of the carbon framework. Zinc nitrate forms ZnO, which volatilizes and creates interconnected channels.

[0021] Furthermore, the polar aprotic solution includes at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N,N-dimethylacetamide (DMAC).

[0022] Furthermore, the mass ratio of the mixture to the aprotic polar solution is 25-40:60-75.

[0023] Furthermore, in step S2, the temperature is increased to 750-850℃ at a heating rate of 3-7℃ / min and held for 1.5-2.5h; the temperature is increased to 1800-2200℃ at a heating rate of 8-12℃ and held for 1.8-2.2h.

[0024] During heat treatment at 750-850℃, the metal salt undergoes thermal decomposition to generate α-Fe₂O₃ / ZnO nanoparticles, which are uniformly distributed within the carbon fiber matrix. During heat treatment at 1800-2200℃, the metal oxide undergoes carbothermic reduction (Fe₂O₃ + 3C → 2Fe + 3CO↑). The volatilized metal vapor forms 100-200 nm interconnected channels within the fiber. After heat treatment at 3000℃, the amorphous carbon is completely transformed into a highly ordered graphite structure.

[0025] Furthermore, the volume ratio of the hydrogen gas to the inert gas is 1:3-5.

[0026] Furthermore, the spherical silicon particles are prepared by radio frequency plasma method, and the particle size distribution CV < 8%; the mass ratio of the spherical silicon particles to the pore-forming fibers is 1:1.2-1.7.

[0027] Furthermore, the spherical silicon particles and the pore-forming fibers are pre-dispersed in a high-speed mixer, and then combined together by a hot isostatic pressing device, a high-pressure sintering furnace, a mechanical pressing device, or a gas-phase reaction furnace.

[0028] Hot isostatic pressing equipment, high-pressure sintering furnace, and mechanical pressing equipment enable the silica melt to fully penetrate into the three-dimensional channels of carbon fibers under capillary action. After cooling, a mechanically interlocked structure is formed in which silicon-carbon particles are embedded in the pores of carbon nanofibers.

[0029] The gas reactor uses nitrogen gas to propagate silicon-carbon particles and carbon fibers at high speed. The silicon particles are diffused and embedded in the pores of the carbon fibers, forming a stable bond.

[0030] The present invention also provides a silicon-carbon material, characterized in that it is prepared by the preparation method described above.

[0031] The present invention also provides a lithium-ion battery, including a negative electrode sheet, the negative electrode sheet comprising the silicon-carbon material as described above.

[0032] This invention provides a method for preparing silicon-carbon materials. A metal salt is mixed with a carbon source to prepare carbon fibers with a large specific surface area and pore size. This increases the specific surface area of ​​the carbon fibers, forming a more stable conductive network and reducing electrode impedance. Combining the carbon fibers with silicon particles allows the excellent mechanical strength of the carbon fibers to suppress the expansion of the silicon-carbon material, reducing electrode thickness rebound under full charge and improving cycle performance. Attached Figure Description

[0033] Figure 1 These are the impedance box plots of the silicon-carbon negative electrode sheets in Example 1 and Comparative Example 1 of this invention;

[0034] Figure 2 These are the impedance box plots of the silicon-carbon negative electrode sheets in Example 2 and Comparative Example 1 of this invention. Detailed Implementation

[0035] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] Example 1

[0037] S1: High-purity lignin sulfonate was used as the carbon source material and mixed with ferric nitrate (Fe(NO3)3) and zinc nitrate to form a dry powder. The high-purity lignin sulfonate accounted for 75% of the total mass of the dry powder, ferric nitrate accounted for 9%, and zinc nitrate accounted for 17%. The dry powder was ball-milled in a planetary ball mill for 12 hours until a mixed powder with uniform particle size distribution (D50 < 10 μm) was obtained. The obtained mixed powder and solvent N,N-dimethylformamide (DMF) were mixed at a mass ratio of 35:65 to form a precursor solution. Subsequently, the precursor solution was spun into continuous fibers with a diameter of 300±50 nm using a high-voltage electrospinning device. The fiber surface exhibited typical thermoplastic polymer characteristics and could be oriented by roller collection, significantly improving the conductivity and mechanical properties of the fiber membrane.

[0038] S2: The obtained continuous fibers were placed in a tube furnace and heated to 800℃ at a precisely controlled temperature rise rate of 5℃ / min under an argon protective atmosphere (flow rate 200 mL / min) and held for 1 hour. During this process, the metal salt underwent a thermal decomposition reaction to generate α-Fe2O3 / ZnO nanoparticles, which were uniformly distributed in the carbon fiber matrix. The temperature was then switched to a hydrogen-argon mixed gas (H2:Ar flow rate ratio of 1:4, total flow rate 250 mL / min) and rapidly increased to 2000℃ at a rise rate of 10℃ / min for high-temperature reduction treatment. This was held for 2 hours to allow the metal oxides to undergo a carbothermic reduction reaction (Fe2O3 + 3C → 2Fe + 3CO↑). The volatilized metal vapor formed 100-200 nm through-channels inside the fibers. Mercury porosimetry testing showed that the material had a hierarchical porosity of 38±2% and a BET specific surface area of ​​520 m² / g. The obtained sample was placed in an ultra-high temperature graphitization furnace (argon protection) and heat-treated at 3000℃ for 4 hours, after which the amorphous carbon was completely transformed into a highly ordered graphite structure.

[0039] S3: 120nm spherical silicon particles (particle size distribution CV < 8%) prepared by radio frequency plasma method were pre-dispersed with porous carbon fibers at a mass ratio of 1:1.5 in a high-speed mixer, and then placed in a hot isostatic pressing device. After cooling, a mechanically interlocked structure of silicon-carbon particles embedded in the pores of carbon nanofibers was formed.

[0040] S4: In a customized CVD system, an acetylene carbon source (flow rate 50 sccm) was used to deposit a 3 nm thick pyrolytic carbon layer at 650 °C. This coating layer is continuous and dense, which improves its initial coulombic efficiency and cycle performance.

[0041] Example 2

[0042] The only difference between this embodiment and Embodiment 1 is that a gas reactor is used for compounding in step S3. The specific operation is as follows:

[0043] S3: 120nm spherical silicon particles (particle size distribution CV<8%) prepared by radio frequency plasma method and porous carbon fibers are subjected to high-speed movement with nitrogen in a gas reactor at a mass ratio of 1:1.5. Under the diffusion effect, the silicon particles will be embedded in the pores of the carbon fibers to form a stable bonded state, and the porosity is 60%, thus obtaining a silicon-carbon composite.

[0044] Comparative Example 1

[0045] Commercially available conventional silicon-carbon.

[0046] Assemble into a negative electrode plate:

[0047] The silicon-carbon material used in Examples 1, 2, or Comparative Example 1 was used as the negative electrode active material with a content of 96 wt%, and the binder was lithium polyacrylate (PAA) with a content of 2 wt%. The styrene-butadiene rubber (SBR) content was 2wt%. The mixture was prepared in three stages using a dual planetary mixer (30 rpm revolution / 2000 rpm rotation): dry mixing (5 min): pre-dispersed powder agglomeration; wet mixing (60 min): NMP solvent gradient addition (final solid content 45-48%); defoaming (15 min): degassing under vacuum of -0.095 MPa. The slurry viscosity was controlled at 4000±500 cP (25℃), and the fineness was measured by a fineness gauge (D100≤25μm). Coating trials were conducted with a surface density controlled at 6.48±0.2 mg / cm² and a coating rate of 0.8 m / min. Rolling shaping was performed with a compaction rate of 1 g / cc, a rolling temperature of 80℃, and a rolling thickness of 72.8±1.5 μm to obtain the silicon-carbon negative electrode sheet.

[0048] Impedance tests were performed on the negative electrode sheets obtained in Example 1, Example 2, and Comparative Example 1, respectively, and the results are as follows. Figures 1-2 .

[0049] like Figure 1 As shown, the average impedance of the conventional silicon-carbon anode sheet in Comparative Example 1 is 0.1274Ω, while the average impedance of the silicon particle-embedded carbon nanofiber anode sheet in Example 1 is 0.0199Ω. Figure 2 As shown, the average impedance of the conventional silicon-carbon negative electrode sheet in Comparative Example 1 is 0.12665Ω, while the average impedance of the silicon particle-embedded carbon nanofiber negative electrode sheet in Example 1 is 0.02945Ω. This demonstrates that the silicon-carbon composite material with silicon particles embedded in carbon nanofibers of the present invention can significantly reduce electrode impedance, which is beneficial for improving the electrical performance of the battery cell.

[0050] Assemble into battery cells:

[0051] The preparation method of the positive electrode sheet is as follows:

[0052] The positive electrode dry powder is prepared from a high-nickel ternary material: PVDF (polyvinylidene fluoride): carbon black: CNT (carbon nanotubes): 96.5: 2: 1: 0.5 ratio. (1) Dissolve PVDF in NMP (N-methylpyrrolidone) to form a colloid with a solid content of 7%. (2) Add carbon black and CNT to the colloid in batches and disperse at high speed to obtain a conductive colloid. (3) Add the high-nickel ternary positive electrode material and disperse at high speed. (4) Adjust the viscosity to the target range of discharge viscosity (6000-8000 mpa·s), take out the slurry and coat-roll-slit-bake to obtain the positive electrode sheet.

[0053] The negative and positive electrode sheets obtained in Examples 1, 2, and 1 (Comparative Example 1) were assembled into semi-solid-state batteries. The thickness of the silicon-carbon negative electrode sheet after baking was measured and recorded as M1 (thickness index: 72.8 ± 1.5). After formation and full charging, it was measured again and recorded as M2. The thickness rebound rate was calculated as (M2 - M1) / M1. The average value was calculated after repeated testing. The test results are shown in Tables 1 and 2.

[0054] Table 1. Full-charge thickness rebound test results of battery cell electrodes in Comparative Example 1 and Example 1

[0055] Comparative Example 1 1 2 3 4 5 6 7 8 Mean Pole piece thickness M1 / pm 72.4 72.5 72.8 73.5 73.2 72.2 72.9 73.1 72.83 Pole piece thickness M2 / pm 101.2 102.1 102.4 102.2 101.8 101.7 101.9 102.0 101.91 Thickness Rebound / % 39.78 40.83 40.66 39.05 39.07 40.86 39.78 39.53 39.95 Example 1 1 2 3 4 5 6 7 8 Mean Pole piece thickness M1 / pm 72.5 72.8 72.9 73.1 72.4 72.7 72.6 71.9 72.61 Pole piece thickness M2 / pm 85.1 86.2 85.7 87.3 86.0 85.9 86.6 86.4 86.15 Thickness Rebound / % 17.38 18.40 17.56 19.42 18.78 18.16 19.28 20.17 18.65

[0056] As shown in Table 1, in the same system, the conventional silicon-carbon anode sheet in Comparative Example 1, under full charge, exhibits a significantly increased thickness rebound rate (average 39.95%) due to the large expansion coefficient of silicon-carbon. This is detrimental to repeated charge-discharge cycles and affects long-term cycle performance. In contrast, the silicon-carbon anode sheet prepared by the silicon particle embedding carbon nanofiber method in Example 1, due to the superior mechanical strength of the carbon nanofibers, suppresses the expansion of silicon-carbon particles embedded in the pores, thus reducing the thickness rebound rate under full charge, with an average of only 18.65%.

[0057] Table 2. Full-charge thickness rebound test results of battery cell electrodes in Comparative Example 1 and Example 2

[0058] Comparative Example 1 1 2 3 4 5 6 7 8 Mean Pole piece thickness M1 / pm 72.8 72.9 73.1 73.3 72.7 72.9 73.5 73.1 73.04 Pole piece thickness M2 / pm 101.1 102.2 101.6 101.9 102 101.7 101.5 101.6 101.7 Thickness Rebound / % 38.87 40.19 38.99 39.02 40.30 39.51 38.10 38.99 39.25 Example 2 1 2 3 4 5 6 7 8 Mean Pole piece thickness M1 / pm 72 72.5 72.7 72.9 73 72.8 73.1 72.5 72.69 Pole piece thickness M2 / pm 81.1 80.8 81 80.5 80.7 81.6 81.4 80.3 80.93 Thickness Rebound / % 12.64 11.45 11.42 10.43 10.55 12.09 11.35 10.76 11.33

[0059] like Figure 2 As shown in Table 2, Comparative Example 1 uses a gas reactor for composite processing. Due to the increased porosity, it has a better effect on suppressing silicon-carbon expansion (thickness rebound rate decreased from 18.65% to 11.33%), and the higher silicon content also increases the specific capacity of the cell. The disadvantage is that the increased porosity leads to the breakage of the carbon skeleton and the thinning of the three-dimensional conductive network, resulting in lower conductivity than the melting method (electrode impedance increased from 0.0199Ω to 0.02945Ω). In actual production, the preparation method will be selected according to the needs of the cell.

[0060] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A method for preparing a silicon-carbon material, characterized in that, Includes the following steps: S1 Preparation of precursor: A carbon source and a metal salt are mixed and dry ball-milled until the particle size D50 of the mixture is <10μm; the mixture is mixed with an aprotic polar solution and spun into continuous fibers with a diameter of 300±50nm by high-voltage electrospinning. S2 pyrolysis and purification: In an inert gas atmosphere, the continuous fiber is heated to 750-850℃ and held at that temperature; then in an atmosphere of hydrogen and inert gas, the temperature is raised to 1800-2200℃ for a high-temperature reduction reaction and held at that temperature; then in an inert gas atmosphere, it is heated to 2800-3200℃ for heat treatment to obtain porous carbon fiber. S3 silicon-carbon composite: Spherical silicon particles with a particle size of 100-150nm are infiltrated into the pores of porous carbon fibers. S3 Carbon Coating: Carbon coating of silicon-carbon composite materials is performed by vapor deposition.

2. The method for preparing a silicon-carbon material according to claim 1, characterized in that, In step S1, the carbon source accounts for 70-85% of the mass of the mixture.

3. The method for preparing a silicon-carbon material according to claim 1, characterized in that, In step S1, the carbon source includes one or more of high-purity lignin sulfonate, alkali lignin, organic solvent lignin, polyaniline, polypyrrole, polyacrylonitrile, and polyvinyl alcohol; the metal salt is a soluble salt of iron and zinc.

4. The method for preparing a silicon-carbon material according to claim 3, characterized in that, The metal salts are ferric nitrate and zinc nitrate; the ferric nitrate accounts for 30-40% of the total mass of the metal salts.

5. The method for preparing a silicon-carbon material according to claim 1, characterized in that, The polar aprotic solution includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide; the mass ratio of the mixture to the aprotic polar solution is 25-40:60-75.

6. The method for preparing a silicon-carbon material according to claim 1, characterized in that, In step S2, the temperature is increased to 750-850℃ at a heating rate of 3-7℃ / min and held for 1.5-2.5h; the temperature is increased to 1800-2200℃ at a heating rate of 8-12℃ and held for 1.8-2.2h; the volume ratio of hydrogen to inert gas is 1:3-5.

7. The method for preparing a silicon-carbon material according to claim 1, characterized in that, The spherical silicon particles are prepared by radio frequency plasma method, and the particle size distribution CV < 8%; the mass ratio of the spherical silicon particles to the pore-forming fibers is 1:1.2-1.

7.

8. The method for preparing a silicon-carbon material according to claim 1, characterized in that, The spherical silicon particles and the porous fibers are combined together using a hot isostatic pressing device, a high-pressure sintering furnace, a mechanical pressing device, or a gas-phase reactor.

9. A silicon-carbon material, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

10. A lithium-ion battery, comprising a negative electrode, characterized in that, The negative electrode comprises the silicon-carbon material as described in claim 9.